2008
DOI: 10.1530/rep-07-0572
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of testicular tight junctions by gonadotrophins in the adult Djungarian hamster in vivo

Abstract: This study aimed to assess the effect of gonadotrophin suppression and FSH replacement on testicular tight junction dynamics and blood-testis barrier (BTB) organisation in vivo, utilising the seasonal breeding Djungarian hamster. Confocal immunohistology was used to assess the cellular organisation of tight junction proteins and real-time PCR to quantify tight junction mRNA. The effect of tight junction protein organisation on the BTB permeability was also investigated using a biotin-linked tracer. Tight junct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 63 publications
(84 reference statements)
8
55
0
Order By: Relevance
“…However, in rats, occludin expression is stage-specific, with immunostain not detectable in Stage VIII tubules but strongly expressed at all other stages (Li et al 2006). Occludin expression is also stage-specific in Djungarian hamsters exposed to long-day photoperiods; the stage distribution was not reported (Tarulli et al 2008). Interestingly, occludin is not expressed in the seminiferous tubules of guinea pigs (Cavia porcellus) and men (Moroi et al 1998).…”
Section: Claudin and Occludin Expression In The Testesmentioning
confidence: 96%
See 2 more Smart Citations
“…However, in rats, occludin expression is stage-specific, with immunostain not detectable in Stage VIII tubules but strongly expressed at all other stages (Li et al 2006). Occludin expression is also stage-specific in Djungarian hamsters exposed to long-day photoperiods; the stage distribution was not reported (Tarulli et al 2008). Interestingly, occludin is not expressed in the seminiferous tubules of guinea pigs (Cavia porcellus) and men (Moroi et al 1998).…”
Section: Claudin and Occludin Expression In The Testesmentioning
confidence: 96%
“…Thus in Djungarian hamsters, increased mRNA expressions of claudins 3 and 11 and occludin do not indicate increased BTB functionality. It was noted that in Djungarian hamsters, the responses of testicular claudins 3 and 11 and occludin to FSH stimulation occur during a time period when intratesticular testosterone levels are low (Tarulli et al 2008). This was interpreted as a difference between Djungarian hamsters and other rodent species regarding the importance of testosterone in establishing and maintaining the BTB.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…The consequences of the shift in Factin and BTB proteins on BTB functionality cannot be predicted because it has been reported that the localization and/or expression of TJ proteins can change over the cycle of the seminiferous epithelium but permeability to the small molecule biotin is still restricted as far as the organized TJ immunoreactivity. 43 The shift, at least for F-actin, is likely not an indirect consequence of germ cell loss because the subcellular distribution of F-actin and intermediate filaments (vimentin) at the BTB is not markedly affected in W/W v mice, which also lack spermatogenic cells. 44,45 …”
Section: Akap9 In Blood-testis Barrier Integritymentioning
confidence: 99%
“…Other than rat models, studies on Djungarian hamsters have also demonstrated that exogenous supply of FSH to short-day photoperiod (8 h light:16 h darkness) hamsters whose gonadotropins are suppressed could restore the localization of junction proteins such as actin and espin at the apical ES, and claudin-11 and zonula occludens-1 (ZO-1) at the basal region of the seminiferous epithelium (Tarulli et al 2006). Using the same animal model, Tarulli et al (2008) have recently found that similar to claudin-11, claudin-3, occludin and JAM-A can rapidly be reorganized at the BTB upon FSH replacement. These results strongly suggest that in addition to spermiation, FSH regulates the integrity and functionality of the BTB via reorganization and relocalization of junction proteins.…”
Section: Fsh and Estrogenmentioning
confidence: 99%